HUBUNGAN ANTARA PEMBERIAN IMUNISASI DASAR DENGAN STATUS GIZI BALITA DI POSYANDU SEROJA DESA SUNGAI UNDANG KABUPATEN SERUYAN PROVINSI KALIMANTAN TENGAH TAHUN 2019 - hardianti aprina (Jurnal Ilmiah Kebidanan dan Kesehatan Wanita, 2020)
ABSTRACT Background : Nutritional status is a condition caused by a balance status between nutrient intake and nutritional needs by the body for various biological processes. Immunization is an indirect factor that affects the nutritional status of children under five. 70% of toddlers who experience malnutrition are found in Asia. Accoding to Riskesdas in 2018 there were 17,7% cases of underfives with malnutritional and this number consisted of 3,9% of toddlers with malnutrition. The Perpouse : Knowing the correlation between giving basic immunization with nutritional status of toodler in Seroja integrade service post at Sungai Undang village Seruyan District of Central Kalimantan Privince in 2019. Methods Research : This study uses quantitative analytical methods with retrospektif design. At conducted in Puskesmas Pembantu Sei Undang in May - September 2019 with the total sample of 96 people using purposive sampling techniques from secondary data. The independent variable is giving basic immunization and the dependent variable is nutrional status. The Result : The result of this research is showed that malnutrition status of 10 people (66,67%) with incompletenes immunization status and the toddler’s have a good nutrional status of 53 people (82,81%) with complete immunization status. Giving of basic immunization has a significant correlation with nutritional status (p = 0,001). Conclusion : The Conclusion of this research so that a there correlation giving basic immunization and nutritional status for toddler’s. The more complete the provision of immunization to toddler’s then he will affect their nutritional status.